2021
DOI: 10.1186/s40560-021-00548-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers in acute respiratory distress syndrome: a systematic review and meta-analysis

Abstract: Background Acute respiratory distress syndrome (ARDS) is a leading cause of morbidity and mortality in the intensive care unit. Biochemical markers of cardiac dysfunction are associated with high mortality in many respiratory conditions. The aim of this systematic review is to examine the link between elevated biomarkers of cardiac dysfunction in ARDS and mortality. Methods A systematic review of MEDLINE, EMBASE, Web of Science and CENTRAL database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Cardiomyocyte injury, quantified by elevated troponin levels, and haemodynamic cardiac stress, as quantified by increased natriuretic peptide concentrations have been previously described both in COVID-19 and ARDS [32][33][34]. The association of NT-proBNP and abnormal troponin levels with RVD in this cohort suggests a potential role of direct myocardial injury in the aetiology of myocardial dysfunction in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…Cardiomyocyte injury, quantified by elevated troponin levels, and haemodynamic cardiac stress, as quantified by increased natriuretic peptide concentrations have been previously described both in COVID-19 and ARDS [32][33][34]. The association of NT-proBNP and abnormal troponin levels with RVD in this cohort suggests a potential role of direct myocardial injury in the aetiology of myocardial dysfunction in patients with COVID-19.…”
Section: Discussionsupporting
confidence: 64%
“…In animal and human studies, it has been stated that when hypoxic pulmonary vasoconstriction is created, BNP increases and causes pulmonary vasodilation. It has been reported that high BNP is associated with an increased risk of death in patients with acute respiratory distress syndrome (ARDS) [ 24 ]. Güllü et al studied cases of envenomation due to scorpion bites and showed proBNP to have a good predictive value for a poor outcome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…NT‐proBNP is currently used as a prognostic indicator in human patients and appears to predict adverse outcomes better than other cardiac biomarkers upon patient follow‐up, suggesting the ability to aid in risk stratification 4 . Additionally, a metanalysis of 18 research studies revealed that high NT‐proBNP concentrations, indicating cardiac stretch, were associated with a higher risk of death due to acute respiratory distress syndrome for up to 60 days 5 . Thus, NT‐proBNP is an important prognosticator for both left heart and right heart overload, which includes either cardiogenic or pulmonogenic etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…4 Additionally, a metanalysis of 18 research studies revealed that high NT-proBNP concentrations, indicating cardiac stretch, were associated with a higher risk of death due to acute respiratory distress syndrome for up to 60 days. 5 Thus, NT-proBNP is an important prognosticator for both left heart and right heart overload, which includes either cardiogenic or pulmonogenic etiologies.…”
Section: Introductionmentioning
confidence: 99%